(untitled) (Plant Tissue Culture and Biotechnology, 2025)
The present study was undertaken to develop an effective protocol for rapid in vitro seed germination and mass propagation of Arundina graminifolia. Four basal media, viz., MS, B5, PM and modified VW, were used for germination of seeds and protocorm development. Here, MS medium showed better performance (89.31 ± 0.98%) in seed germination than that of the others. In vitro grown plantlets with 2-3 leaves were considered as explants for multiple shoot buds (MSBs) induction and its subsequent development and for that various concentration of PGRs (Kn, BAP and NAA) either single or in combination were used in MS medium. The maximum number of secondary protocorm like bodies (PLBs) (80 ± 0.32%) and shoots (90 ± 0.45%) were recorded on MS medium supplemented with 1.0 mg/l Kn + 1.0 mg/l NAA and 1.0 mg/l BAP respectively. The highest number (14.10 ± 0.21) of secondary PLBs was generated on MS medium in presence of 1.0 mg/l Kn and 1.0 mg/l NAA. Maximum length (4.59 ± 0.14 cm) of plantlets was also obtained on MS medium enriched with 1.5 mg/l BAP and 0.75 mg/l NAA, while a maximum (11.50 ± 0.32) shoots per explant were recorded on the same medium fortified with 1.0 mg/l Kn and 0.5 mg/l NAA. The elongated shoots were transferred on ½MS medium in addition to specific plant growth regulators (PGRs) for root development, where four concentrations (0.5-2.0 mg/l) of PGRs were used. Data showed that the ½MS medium + 1.0 mg/l NAA gave better results on number of roots (9.03 ± 0.26) induction as well as their length (4.92 ± 0.10 cm). Well-rooted plants were transferred to pots after acclimatization. This reproducible protocol can be used for further mass multiplication and applied research in the orchid development in Bangladesh. Plant Tissue Cult. & Biotech. 35(1): 67-80, 2025 (June)